Evaluation of Titration Method on Determination of Ozone Concentration produced by Dielectric Barrier Discharge Plasma (DBDP) Technology. (February 2019) - Chasanah, U; Yulianto, E; Zain, A Z; Sasmita, E; Restiwijaya, M; Kinandana, A W; Arianto, F; Nur, M
Abstract: Determination of the ozone concentration produced by a reactor is very important. The titration method is an analytical chemical method with high accuracy still in use. Research on titration for measurement of ozone concentration generated by a generator at a given flow rate has been done. Ozone is produced by a dielectric barrier discharge plasma reactor. The reactor is formed with a cylindrical-cylindrical electrode configuration made of stainless steel wire mesh. Evaluation of ozone concentration of titration method was done by varying air flow rate between 4-15 liter/min. The titration time is varied between 3-12 minutes. Voltage source was used a high-voltage AC with variation between 6 - 11 kV. The greater the air flow rate the resulting ozone concentration will decrease. The concentration of ozone obtained is smaller with a large tear time at the same voltage and flow rate. From the results of this study, the time of titration in determining the concentration of ozone is not required larger, at 3 minutes has given the best results. The long of titration time probably the ozone dissolve and saturated in the titrant (KI) and released into the air again.